CHALLENGES OF DEMOCRACY IN THE DIGITAL ERA: THE ROLE OF SOCIAL MEDIA IN ELECTIONS AND POLITICAL POLARIZATION - Sanwonglakron, Chatthasanan; Wareewarach, Ruangwit (Journal of MCU Nakhondhat, 2025)
Democracy in the digital age faces increasingly complex challenges, particularly regarding the role of social media in influencing electoral processes and deepening political divisions. This article examines key issues arising from social media use, including the spread of fake news, disinformation, and political polarization, which significantly impact voter behavior and political stability. Case studies such as the U.S. presidential elections and the Brexit process illustrate the profound effects of social media on democratic processes. One of the most pressing concerns is the rapid and widespread dissemination of false information. Social media platforms powerful tools for shaping public opinion through algorithms that curate content based on preferences. This results in the phenomenon known as the "echo chamber," where individuals are repeatedly exposed to similar viewpoints, reinforcing political extremism and reducing opportunities for balanced discourse. Furthermore, the lack of appropriate regulatory measures allows interest groups to manipulate these platforms, steering or distorting information to serve their political agendas. To address these challenges, a comprehensive approach is essential. Key solutions include developing transparent and unbiased algorithms, implementing regulatory oversight of digital content by governments and independent organizations, promoting media literacy among citizens, and fostering collaboration between governments, private sectors, and civil society organizations to create a digital ecosystem that supports democratic values. Maintaining a balance between freedom of expression and democratic stability in the digital age requires the collective efforts of all stakeholders. It is crucial to ensure that technology a positive force in strengthening democracy rather than a tool that undermines political stability.